O przemieniającym życie mroku postaci - WIERZCHOWSKI, MARCIN (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
On the darkness of the character that transforms life The author analyses the relationship between the actor>s life and the character they create on stage. He points to the interdependencies between the actor and their role. He determines the conditions in which the role should be constructed and also discusses the on- and off-stage circumstances that determine the value of a particular role. This analysis is supported by the authors own experience as a theatre director.